Epimeric Face-Selective Oxidations and Diastereodivergent Transannular Oxonium Ion Formation Fragmentations: Computational Modeling and Total Syntheses of 12-Epoxyobtusallene IV, 12-Epoxyobtusallene II, Obtusallene X, Marilzabicycloallene C, and Marilzabicycloallene D - Clarke,J; Bonney,KJ; Yaqoob,M; Solanki,S; Rzepa,HS; White,AJP; Millan,DS; Braddock,DC (Journal of Organic Chemistry, 2016)
The total syntheses of 12-epoxyobtusallene IV, 12-epoxyobtusallene II, obtusallene X, marilzabicycloallene C, and marilzabicycloallene D as halogenated C15-acetogenin 12-membered bicyclic and tricyclic ether bromoallene-containing marine metabolites from Laurencia species are described. Two enantiomerically pure C4-epimeric dioxabicyclo[8.2.1]tridecenes were synthesized by E-selective ring-closing metathesis where their absolute stereochemistry was previously set via catalytic asymmetric homoallylic epoxidation and elaborated via regioselective epoxide-ring opening and diastereoselective bromoetherification. Epimeric face-selective oxidation of their Δ12,13 olefins followed by bromoallene installation allowed access to the oppositely configured 12,13-epoxides of 12-epoxyobtusallene II and 12-epoxyobtusallene IV. Subsequent exploration of their putative biomimetic oxonium ion formation-fragmentations reactions revealed diastereodivergent pathways giving marilzabicycloallene C and obtusallene X, respectively. The original configurations of the substrates evidently control oxonium ion formation and their subsequent preferred mode of fragmentation by nucleophilic attack at C9 or C12. Quantum modeling of this stereoselectivity at the ωB97X-D/Def2-TZVPPD/SCRF = methanol level revealed that in addition to direction resulting from hydrogen bonding, the dipole moment of the ion-pair transition state is an important factor. Marilzabicycloallene D as a pentahalogenated 12-membered bicyclic ether bromoallene was synthesized by a face-selective chloronium ion initiated oxonium ion formation-fragmentation process followed by subsequent bromoallene installation.